Complete Genome Sequence of Leisingera aquamixtae R2C4, Isolated from a Self-Regenerating Biocathode Consortium - Bird, Lina (Microbiol Resour Announc, 2019)
Here, we present the complete genome sequence of Leisingera aquamixtae R2C4, isolated from the electroautotrophic microbial consortium biocathode MCL (Marinobacter-Chromatiaceae-Labrenzia). As an isolate of a current-producing system, the genome sequence of L. aquamixtae will yield insights regarding electrode-associated microorganisms and communities. A dark pigment is also observed during cultivation.